Enhancing Urban Transit Oriented Development: Investigating Passenger Loyalty, Attitudes, and Perceived Usefulness on Jabodetabek KAI Commuter - Megawati, Hermeilia; Aegista, Roza Alifia; Widyastuti, Liza Yudhita; Putri, Alifa Syamantha (UI Scholars Hub, 2025)
This study explores the psychological factors that influence applying a technology acceptance model to KAI Commuter Jabodetabek. The model focuses on the primary variables of perceived usefulness and attitude toward the service, with passenger loyalty serving as the key indicator of successful public transportation acceptance. Data was collected via surveys from 352 purposively selected commuter workers in the Greater Jakarta area using a cross-sectional, quantitative design. The measurement tools used are adaptations of the Passenger Loyalty Measure to Public Transportation Modes, the Attitude Measure to Public Transportation, and the Perceived Usefulness Measure. The results indicate that attitude toward KAI Commuter Jabodetabek partially mediates the relationship between perceived usefulness and passenger loyalty (B = 1.2, t = 7.35, p < .001). This indicates that passengers’ decision to use or reject KAI Commuter Jabodetabek services depends on the ratio of benefits. By integrating principles from the technology acceptance model with psychological theories of attitude and behavior, this study addresses a critical gap in understanding how psychological and perceptual factors drive transit behavior. The insights gained provide valuable guidance for the design and management of PTSs , enhancing user adoption and long-term loyalty.